Empirical models challenging biblical criticism - Person, Raymond F.; Rezetko, Robert (Ancient Israel and its literature, 2016)
Cover; Contents; Abbreviations; Introduction; Outsourcing Gilgamesh; Scribal Revision and Textual Variation in Akkadian Suila-Prayers ; Dissimilatory Reading and the Making of Biblical Texts; Text-Critically Studying the Biblical Manuscript Evidence; Division Markers as Empirical Evidence for the Editorial Growth of Biblical Books ; The Problem of "Literary Unity" From the Perspectives of the Study of Oral Traditions ; The (Dis)Connection between Textual and Linguistic Developments in the Book of Jeremiah ; The Original Problem; Community Rule or Community Rules